Penanaman Modal Asing dan Keterbukaan Perdagangan Terhadap Pertumbuhan Ekonomi Indonesia Tahun 2015-2024 - M. Nashrullah; Resty Abdillah Paryanda; Lina Trisnawati; Rokhmat Subagiyo; Muhammad Aswad (JOURNAL OF SHARIA ECONOMICS, 2022)
This study applies a multiple linear regression model. The results of the study show that simultaneously, FDI and Trade openness are proven to contribute positively and significantly to Economic Growth with a calculated F value of 7.985 > F table 5.318 and a Sig. value of 0.016 < 0.05. However, partial analysis shows that FDI, although showing a positive direction, does not have a significant influence on economic growth with a calculated T value of 1.913 > T table 1.860 and Sig. 0.097 > 0.05. In contrast, Trade Openness has a positive and statistically significant impact with a calculated T value of 3.933 > T table 1.860 and Sig. 0.006 < 0.05. With the model's ability to explain 60.8% of the variation in Economic Growth, this study implies that Trade Openness currently plays a more dominant and stable role than FDI in driving the Indonesian economy. These findings have policy implications: the government needs to balance foreign investment promotion strategies with strengthening the domestic export structure and increasing national industrial capacity to ensure a more productive impact of FDI. Future research is recommended to expand the variables to include factors such as institutional quality, political stability, and the ease of doing business index to obtain a more comprehensive picture.